Allergic diseases and cardiovascular diseases: A mendelian randomization study - Wang, Mingming; Wang, Dong; Liao, Yongchao; Li, Ruipeng; Zhong, Yufei; Zhang, Jiayuan (Jour Med Resh and Health Sci, 2024)
Background: Prior observational and experimental research has established an association between allergic diseases and cardiovascular diseases (CVDs), yet the causal relationship remains elusive. Our study utilized Mendelian randomization (MR) to investigate the potential causality between allergic diseases and CVDs. Methods: The exposure and outcome datasets were sourced from the IEU Open GWAS project (https://gwas.mrcieu.ac.uk/). The exposure dataset comprised data on allergic diseases, including allergic rhinitis, childhood-onset asthma, adult-onset asthma, dermatitis and eczema. The outcome dataset consisted of data on CVDs, specifically coronary artery disease (CAD), ischemic stroke (IS), and congestive heart failure (CHF). The primary analysis employed the Inverse Variance Weighted (IVW) method, complemented by sensitivity analyses including MR-Egger, Cochrane’s Q test, MR-PRESSO, and leave-one-out to enhance the results’ reliability. Result: Utilizing the IVW method, the MR analysis unveiled a genetically predicted association between allergic rhinitis and CVDs (OR=0.989; 95% CI =0.980-0.999, P=0.031), as well as coronary artery disease (CAD) (OR=0.944; 95% CI =0.8914-0.9995, P=0.048). Similarly, a significant association emerged between childhood-onset asthma and CVDs (OR=0.99993; 95% CI =0.9989-0.9998, P=0.003) and CAD (OR=0.996; 95% CI =0.993-0.999, P=0.023). Conclusion: This study offers preliminary evidence indicating a slight reduction in CADs risk associated with specific allergies. Additional studies are necessary to confirm these preliminary results and to investigate their significance for the prevention of CVDs.